2020
DOI: 10.5194/tc-2020-332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a swath-to-swath sea-ice drift product for the Copernicus Imaging Microwave Radiometer mission

Abstract: Abstract. Across spatial and temporal scales, sea-ice motion has implications on ship navigation, the sea-ice thickness distribution, sea ice export to lower latitudes and re-circulation in the polar seas, among others. Satellite remote sensing is an effective way to monitor sea-ice drift globally and daily, especially using the wide swaths of passive microwave missions. Since the late 1990s, many algorithms and products have been developed for this task. Here, we investigate how processing sea-ice drift vecto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The mean value of correlation coefficient of comparison between three KIMURAnew datasets and three buoys is 0.93, and of regression slope 255 is 0.97. We notice that comparison of KIMURAnew with the Ross Sea buoy (Table 2) exhibits relatively large RMSD (4.4 to 5.8 km day -1 ), considerably larger than that of the two Weddell Sea buoys (from 2.0 to 3.7 km day -1 ), as well as larger than the validation of DM-derived sea ice motion RMSD (from 2.3 to 2.9 km day -1 ) from Lavergne et al (2020). This difference in RMSD prompted further investigation into the performance difference between the Ross and Weddell seas.…”
Section: Validation Of Kimuranew Datasetsmentioning
confidence: 74%
See 4 more Smart Citations
“…The mean value of correlation coefficient of comparison between three KIMURAnew datasets and three buoys is 0.93, and of regression slope 255 is 0.97. We notice that comparison of KIMURAnew with the Ross Sea buoy (Table 2) exhibits relatively large RMSD (4.4 to 5.8 km day -1 ), considerably larger than that of the two Weddell Sea buoys (from 2.0 to 3.7 km day -1 ), as well as larger than the validation of DM-derived sea ice motion RMSD (from 2.3 to 2.9 km day -1 ) from Lavergne et al (2020). This difference in RMSD prompted further investigation into the performance difference between the Ross and Weddell seas.…”
Section: Validation Of Kimuranew Datasetsmentioning
confidence: 74%
“…To fully and accurately represent sea ice kinematics, some avenues for targeted research pathways are suggested here. From recent research, S2S-derived sea ice trajectories obtained from AMSR2 imagery have been found to be more accurate than the DM-derived equivalents (Lavergne et al, 2020). However, S2S products give better coverage of sea ice motion dataset in the Arctic compared to the Antarctic due to Antarctic sea ice existing at lower latitudes.…”
Section: Future Development Of Ice Kinematics Representationmentioning
confidence: 99%
See 3 more Smart Citations